معرفات البیانات المترابطة والمکتبات :القصة حتى الآن - محمد عبد الحمید معوض (المجلة الدولية لعلوم المكتبات والمعلومات)
The linked data movement is a relatively new trend on the web that,among other things, enables diverse data providers to publish their contentin an interoperable, machine-understandable way. Libraries around theworld appear to be embracing linked data technologies that render theircontent more accessible to both humans and computers. This paperfocuses on linked data URIs that refer to authority data. We attempt toidentify the specific MARC fields that are capable of hosting linked datainformation. Additionally, seven major national libraries are examined todetermine to what degree they have adopted the fundamental linked dataprinciples.